RIFM fragrance ingredient safety assessment, 1-(2, 4, 4, 5, 5-pentamethyl-1-cyclopenten-1-yl)ethan-1-one, CAS Registry Number 13144-88-2. (August 2019) - Api, A.M.; Belmonte, F.; Belsito, D.; Biserta, S.; Botelho, D.; Bruze, M.; Burton, G.A.; Buschmann, J.; Cancellieri, M.A.; Dagli, M.L.; Date, M.; Dekant, W.; et al.
Highlights: 1-(2, 4, 4, 5, 5-pentamethyl-1-cyclopenten-1-yl)ethan-1-one; a safety assessment based on RIFM's criteria. A safety assessment based on 7 human health endpoints plus environmental. All endpoints were cleared using target data, read-across, and/or TTC.